Prognostic value of post-discharge depression in patients recently hospitalized with acute heart failure - Li, Junlei; Jiang, Chao; Liu, Rong; Lai, Yiwei; Li, Li; Zhao, Xiaoyan; Wang, Xiaofang; Li, Ling; Du, Xin; Ma, Changsheng; Dong, Jianzeng (Frontiers in Cardiovascular Medicine, 2022)
Background Depression is a prevalent comorbidity in patients with heart failure (HF). However, data regarding the prognostic significance of depression during the early post-discharge period in patients hospitalized with acute HF, regardless of left ventricular ejection fraction (LVEF), were scarce. Methods and results The Heart Failure Registry of Patient Outcomes (HERO) study is a prospective, multicenter study of patients hospitalized with acute HF in China. At the first follow-up after discharge (median 4.0, interquartile range [IQR]: 2.4–6.1 weeks), depressive symptoms over the past 2 weeks were assessed using the Patient Health Questionnaire-9 (PHQ-9). Of 3,889 patients, 480 (12.3%) patients had depression (PHQ-9 score ≥ 10). A total of 3,456 patients (11.4% with depression) were included in the prospective analysis. After a median follow-up of 47.1 weeks (IQR: 43.9, 49.3) from the first follow-up, 508 (14.7%) patients died, and 1,479 (42.8%) patients experienced a composite event (death or HF rehospitalization). Cox proportional hazards models were used to assess the association of post-discharge depression with adverse events. After adjustment, post-discharge depression was associated with an increased risk of all-cause mortality (hazard ratio [HR] 2.38 [95% confidence interval (CI): 1.93–2.94]; p < 0.001) and the composite event (HR 1.78 [95% CI: 1.55–2.05]; p < 0.001). A per scale point increase in PHQ-9 score (ranging from 0 to 27 points) was associated with a 7.6% increase in all-cause mortality (HR 1.08 [95% CI: 1.06–1.09]; p < 0.001). In the subgroup analysis, the association between depression and the composite event was significantly stronger in relatively younger patients (< 75 vs. ≥ 75 years; p for interaction = 0.011), and the association between depression and all-cause mortality was significantly stronger in patients with preserved ejection fraction than in those with reduced ejection fraction (p for interaction = 0.036). Conclusion Post-discharge depression in patients recently hospitalized with acute HF is associated with an increased risk of adverse events, regardless of LVEF. Screening for depressive symptoms during the early post-discharge period may help to better identify high-risk patients and tailor patient management. Further studies are needed to determine how regular depression screening can help improve patient management and clinical outcomes.